Guidelines for integrating gender concerns in the development processes a manual for the Philippine Development Plan for Women implementation in Northern Mindanao. (National Commission on the Role of Filipino Women, 1998)
A manual for spatial and socio-economic gender responsive planning, programming and monitoring in the government and private sectors.